Schiff bases and schiff base metal complexes: from syntheses to applications (Journal of Basic and Applied Research in Biomedicine, 2022)
The synthesis and applications of Schiff bases and their metal complexes have attracted much interest and concern in all aspects of chemistry and related fields such as biology and physics. As versatile ligands, Schiff bases are formed when carbonyl compounds (aldehydes or ketones) are condensed with amines. Schiff bases and their metal complexes have been used in quantitative analysis, photometric analysis, flourometry, as potentiometric sensors, in solvent extraction, as solid phase extraction sorbent, in high performance liquid chromatography, in antimicrobial studies, as plant growth regulators, as insecticides, as catalyst, in antifertility and enzymatic activity, as dyes, polymer and other miscellaneous applications. There are limited papers on the applications of Schiff bases and their metal complexes. This review summarizes the preparation of Schiff bases as donors and stabilizers of metals in high oxidation state and their applications.